Dukungan Kesehatan Jiwa dan Psikososial Berbasis Desa Adat Terhadap Dampak Pandemi COVID-19 di Kabupaten Karangasem Bali - I Nengah Sumirta; I Wayan Candra; IGA Harini; Ketut Sudiantara (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
A new history for the whole world that the COVID-19 pandemic brought many changes in human life, not only in the health sector, but also in the economy, education, religion, politics, and others, as well as changes in all sides of human life, both physical, social, mentally and spiritually. In terms of mental health, it is feared that a tsunami of mental health disorders will hit human life during or after the end of the pandemic. This is very worrying if it does not get a fast, precise and correct treatment from all parties. One of the efforts is to increase the participation of rural communities by involving youth organizations in providing treatment. This type of research was pre-experimental with a pre-test and post-test design with a control group. The research population was village youth organizations, with a sample size of 80 people, selected by purposive sampling technique. The independent variable was education-training; while the dependent variables of the study were depression, anxiety, and stress as a result of the COVID-19 pandemic, level of knowledge about the COVID-19 pandemic and competence. The data collection instrument were the Depression Anxiety Stress Scale (DASS), a knowledge test and a competency observation sheet for positive self-talk. Data were analyzed using paired sample t-test. The results of the study illustrate that there was an increase in the number of cases of depression, anxiety and stress in people affected by the COVID-19 pandemic. From the results of education and training there was an increase in the average level of knowledge after treatment, namely 13.6, with a p-value of 0.000. The results of observations on competence obtained that there was an increase in ability. The results of this study illustrate the influence of education and training on the level of knowledge and ability of research subjects in providing treatment for mental health and psychosocial problems that arise as a result of the COVID-19 pandemic.Keywords: mental health and psychosocial; the COVID-19 pandemic; young man ABSTRAK Sejarah baru bagi seluruh dunia bahwa pandemi COVID-19 membawa banyak perubahan dalam kehidupan manusia, tidak hanya dalam bidang kesehatan, tetapi juga ekonomi, pendidikan, agama, politik, dan yang lainnya, serta perubahan di semua sisi kehidupan manusia, baik fisik, sosial, mental dan spiritual. Dari segi kesehatan mental, dikhawatirkan gelombang tsunami gangguan kesehatan jiwa akan melanda kehidupan manusia selama atau setelah berakhirnya pandemi. Hal ini sangat mengkhawatirkan kalau tidak mendapat penanganan yang cepat, tepat dan benar dari semua pihak. Salah satu upaya adalah meningkatkan peranserta masyarakat desa adalah melibatkan organisasi pemuda dalam memberikan penanganan. Jenis penelitian ini adalah pra eksperimen dengan desain pre test and post test with control group. Populasi penelitian adalah organisasi pemuda desa, dengan ukuran sampel 80 orang, yang dipilih dengan teknik purposive sampling. Variabel independen adalah pendidikan-latihan; sedangkan variabel dependen penelitian adalah depresi, anxiety, dan stress sebagai dampak pandemi COVID-19, tingkat pengetahuan tentang pandemi COVID-19 dan kompetensi. Instrumen pengumpulan data adalah Depression Anxiety Stress Scale (DASS), test pengetahuan dan lembar observasi kompetensi. Data dianalisis menggunakan paired sample t-test. Hasil penelitian menggambarkan ada peningkatan jumlah kasus depresi, anxiety dan stress pada masyarakat terdampak pandemi COVID-19. Dari hasil pendidikan dan latihan ada peningkatan rerata tingkat pengetahuan sesudah perlakuan yaitu 13,6, dengan p-value 0,000. Hasil observasi terhadap kompetensi diperoleh ada peningkatan kemampuan. Hasil penelitian ini menggambarkan adaya pengaruh pendidikan dan latihan terhadap tingkat pengetahuan dan kemampuan subjek penelitian dalam memberikan penanganan terhadap masalah kesehatan jiwa dan psikososial yang muncul akibat dari pandemi COVID-19.Kata kunci: kesehatan jiwa dan psikososial; pandemi COVID-19; pemuda